2017
DOI: 10.1159/000454955
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu's Arteritis with Isolated Pulmonary Artery Involvement in a Middle-Aged Asian Woman with Hepatitis B and Latent Tuberculosis Infection

Abstract: We report a rare case of Takayasu's arteritis with isolated pulmonary artery stenosis in the presence of active hepatitis B and latent Mycobacterium tuberculosis infection in a middle-aged Asian woman who initially presented with severe dyspnea on exertion and recurrent syncope, occasional burning chest pains, and fatigue. Therapy of the active hepatitis B and latent M. tuberculosis infection together with a course of methotrexate led to a slight reversal of the symptoms, as angioplasty with or without stentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Over many years, many studies show shreds of evidence implicating the contribution of Mycobacterium tuberculosis in the pathogenesis of TAK [21]. Our studies found 65 cases of latent tuberculosis in patients diagnosed with TAK [11,16,17,[19][20][21][22][23]26,28]. We discovered that the majority of these observational studies detected latent tuberculosis in a patient diagnosed with TAK.…”
Section: Latent Tuberculosis In Tak Patientsmentioning
confidence: 70%
See 4 more Smart Citations
“…Over many years, many studies show shreds of evidence implicating the contribution of Mycobacterium tuberculosis in the pathogenesis of TAK [21]. Our studies found 65 cases of latent tuberculosis in patients diagnosed with TAK [11,16,17,[19][20][21][22][23]26,28]. We discovered that the majority of these observational studies detected latent tuberculosis in a patient diagnosed with TAK.…”
Section: Latent Tuberculosis In Tak Patientsmentioning
confidence: 70%
“…To better understand the role of Mycobacterium tuberculosis in patients diagnosed with Takayasu's arteritis, we studied 13 previously published articles, which in total included 196 patients diagnosed with Takayasu's arteritis [11,16,17,[19][20][21][22][23][24][25][26][27][28]. Out of which 68 had either a prior or current tuberculous infection [11,16,17,[19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations